The divine lawmaker : lectures on induction, laws of nature, and the existence of God - Foster, John, 1941 May 5- (Oxford : Clarendon Press ; New York : Oxford University Press, 2004)
"John Foster presents a clear and powerful discussion of a range of topics relating to our understanding of the universe: induction, laws of nature, and the existence of God. He begins by developing a solution to the problem of induction - a solution that involves the postulation of laws of nature, as forms of natural necessity. He then offers a radically new account of the nature of such laws and the distinctive kind of necessity they involve. Finally, he uses this account as the basis for an argument for the existence of God as the creator of the laws and the universe they govern." "It will be of interest to philosophers and students of philosophy; philosophically-minded theologians; others interested in issues about the 'meaning of life' and the existence of God."--BOOK JACKET
Lecture 1. The Problem of Induction -- Lecture 2. Some Attempted Solutions -- Lecture 3. The Nomological-Explanatory Solution -- Lecture 4. Two Objections to NES -- Lecture 5. The Problem of Laws -- Lecture 6. Armstrong's Theory
Slightly revised versions of lectures given at University of Oxford under title: Induction, laws of nature, and the existence of God
Includes bibliographical references (pages 185-187) and index
Also available on the Internet to subscribing institutions
Keywords: Theism; God -- Proof, Ontological; Necessity (Philosophy); Induction (Logic)